2003
DOI: 10.1021/bm034371u
|View full text |Cite
|
Sign up to set email alerts
|

Solution Properties of Gellan Gum:  Change in Chain Stiffness between Single- and Double-Stranded Chains

Abstract: Nine samples of gellan gum in the sodium form, ranging in weight-average molar mass from 3.47 x 10(4) to 1.15 x 10(5) at 40 degrees C, were investigated by static and dynamic light scattering and viscometry in 25 mM aqueous NaCl both at 40 and at 25 degrees C. The ratios of the molar mass at 25 degrees C (in the ordered state) to that at 40 degrees C (in the disordered state) were in the range of 1.99 to 2.07, supporting the scheme of the conformational transition of gellan gum between a disassociated single c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
0
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 47 publications
5
21
0
8
Order By: Relevance
“…In the case of sodium-type gellan, the value was determined to be 1.3 at 25 C in the 25 mmol kg À1 NaCl aqueous solution. 30 The ratio of the molecular weight of unreleased and released gellan chains was evaluated to be ca. 3.5 assuming that ¼ 1:3 and that the value is independent of the type of counter ion and salt concentration added.…”
mentioning
confidence: 99%
“…In the case of sodium-type gellan, the value was determined to be 1.3 at 25 C in the 25 mmol kg À1 NaCl aqueous solution. 30 The ratio of the molecular weight of unreleased and released gellan chains was evaluated to be ca. 3.5 assuming that ¼ 1:3 and that the value is independent of the type of counter ion and salt concentration added.…”
mentioning
confidence: 99%
“…The weight average molar masses (M w ) for the Nagellan samples obtained in this study are shown in 32 reported that the molar mass dependence of intrinsic viscosity of Na-gellan in aqueous solutions with 25 mM NaCl at 408C was described by the Yamakawa-Fujii-Yoshizaki (YFY) theory 38,39 for an unperturbed wormlike chain using the values of persistence length q ¼ 9.4 nm, molar mass per unit contour length of the chain M L ¼ 355 nm…”
Section: Temperature Dependence Of the Conformational Properties Of Nmentioning
confidence: 82%
“…The value of persistence length for the Na-gellan chain was 9.4 nm and the Na-gellan chain behaves as a semiflexible chain at 408C. 32,40 It is considered that the substantial stiffness of the single-stranded Na-gellan chain facilitates the coil-to-double-helix transition in the allor-none type. In this study, even at the highest polymer concentration (c p ¼ 1.0 wt %), the Na-gellan solution did not form gels due to an insufficient number of helices to form a three-dimensional network.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations